Sea cruises as a new branch of the tourism industry - Ptaszycka-Jackowska, Danuta (Turyzm/Tourism, 2012)
The article presents sea cruises - a form of tourism which is not very common in Poland but flourishes in other parts of the world. The author describes world and European fleets, cruise routes, ports visited and elements of cruise organization. She presents a detailed illustration of the most powerful European company - the Italian Costa Crociere (Costa Cruises) - which organizes cruises in Europe and all over the world.